Quintilianus' Educational Program with Modern Accents - Putkaradze, Ketevan (Bulletin of Akaki Tsereteli State University, 2025)
In this article we try to show how ancient is modern. The ideas and methods of the Roman author, Marcus Fabius Quintilianus, his Educational Program, attitude towards children and requirements for teachers, what should be taught and how, when should be included in the school, private school is better or public, learning through games - or rigorously, whether foreign languages ​​should be learned or not, whether music is the main subject of the educational program and others.